Die Vergangenheitstempora im Alemannischen Deutschlands: eine korpusbasierte quantitative und qualitative Untersuchung - Leonhard, Jens (Empirische Linguistik, 2022)
"In this volume, corpus-linguistic methods and spontaneous language data have been utilized to prove that the tense forms preterite and pluperfect have reestablished themselves in German Alemannic. The reason for this is the influence of standard language. The partial reversal of the disappearance of the preterite is not process of suppression; rather, the four tenses praeterite, perfect, pluperfect and double perfect form a complementary system."--Publisher's website